Relationship Between Circulating Cytokines And Crohn‘S Disease Development In Patients From Baghdad City - Rashid, Khaleel I.; Mahmood, Eman S; J. Naef, Majeed; K.yunis, Sarah (Journal of Neonatal Surgery, 2025)
This study was conducted in Baghdad city to evaluate the relationship between the circulatory cytokines association with crohn‘s disease. The cytokines levels and activity were studied on five cytokines; lL-23, IL-12, IL-6 and INF-γ, TNF-α. Circulating cytokines values were compared according to the disease activity in active and queisnt phases. Results showed that IL-23 significantly the higher level as compared to other cytokines in CD patients, followed by INF-γ. The lower value was found in IL-2 as compared to others. In the other hand, cytok9nes activity in active and queicent phases in the CD patients IL23 showed the high value, where as, TMF-α was recorded the moderate value, and the lower value was recorded to IL-12 as compared to the active and quiescent phases. The differences were not statistically significant. The study showed the association of some circulating cytokines and Crohn’s disease in patients, further studies are needed to determine the effects of the cytokine IL-23 and INF- γ in management of CD and IBD diseases.